Intestinal helminthiasis survey with emphasis on schistosomiasis in Koga irrigation scheme environs, northwest Ethiopia. - Zemenu Tamir; Abebe Animut; Sisay Dugassa; Araya Gebreselassie; Aster Tsegaye; Tesfu Kassa; Tadesse Eguale; Tadesse Kebede; Yohannes Negash; Zeleke Mekonnen; Berhanu Erko (PLoS ONE, 2022)
Background Distribution of schistosomiasis is more focal due to spatial heterogeneities in intermediate host snail dynamics and water contact behavior of humans. This makes the search for new transmission foci of schistosomiasis and its connection with malacologically receptive water bodies essential for effective control of its transmission. This study was intended to assess the prevalence of intestinal helminth infections among schoolchildren and Schistosoma mansoni transmission in Koga irrigation scheme surroundings, northwest Ethiopia. Materials and methods Cross-sectional parasitological and malacological surveys were conducted in three schools and nearby water bodies, respectively around Koga irrigation scheme. Stool specimens were collected from 421 randomly selected schoolchildren and microscopically examined using Kato-Katz and formol-ether concentration methods. Malacological surveys were carried out and the identified Biomphalaria pfeifferi snails were screened for schistosome infection. Swiss albino mice were exposed to schistosome cercariae shed by Biomphalaria pfeifferi for definite identification of Schistosoma species. Results Among the examined schoolchildren, 22.6% (95% CI: 18.7%-26.9%) were positive for at least one intestinal helminths species. Ascaris lumbricoides was the most frequent intestinal helminth detected among forty (9.5%) children. Schistosoma mansoni was detected among 4.8% (95% CI: 2.9%-7.2%) of children and its prevalence was significantly higher among male children (p = 0.038) and those attending in Mengesha Jemberie Primary School (p = 0.044). Biomphalaria pfeifferi snails were identified in water bodies in close proximity to Mengesha Jemberie and Wotete Abay Primay schools. Schistosoma mansoni adult worms were harvested after exposure of mice to cercariae shed from Biomphalaria pfeifferi snails collected from water bodies nearby Mengesha Jemberie Primary School. Conclusions Schistosoma mansoni infection of schoolchildren, findings of schistosome infected snails and establishment of mice infection confirm that transmission is taking place in the study areas. Hence, snail control and other measures such as provision of sanitary facilities and health education are recommended.